Real-World Data of Trifluridine/Tipiracil for Patients With Advanced Gastric Cancer: A Multi-Institutional Retrospective Study. (November 2022) - Matsumoto, Toshihiko; Yamamura, Shogo; Ikoma, Tatsuki; Kurioka, Yusuke; Doi, Keitaro; Yasuda, Tomoyo; Boku, Shogen; Kawai, Takashi; Shibata, Nobuhiro; Nagai, Hiroki; Tsuduki, Takao; Shimada, Takanobu; et al.
Background: A trial with trifluridine/tipiracil (FTD/TPI) versus placebo in patients with heavily pretreated metastatic gastric cancer showed that FTD/TPI is effective with manageable toxicity in these patients. However, real-world data on the effects of FTD/TPI in patients with advanced gastric cancer (AGC) are limited. Methods: We retrospectively collected and analyzed the clinicopathological data of patients with AGC who received FTD/TPI monotherapy at our institutions (Kobe City Medical Center General Hospital, Osaka Red Cross Hospital, Himeji Red Cross Hospital, and Kansai Medical University Hospital) between September 2019 and July 2021. Tumor responses were evaluated based on the Response Evaluation Criteria in Solid Tumors, version 1.1. Overall survival (OS) and progression-free survival were estimated using the Kaplan-Meier method. Results: A total of 53 patients were included in the study. The median age was 70 (range, 37-85) years; 39 patients (74%) were men; the numbers of patients with Eastern Cooperative Oncology Group performance status scores of 0, 1, and 2 were 10 (19%), 39 (74%), and 4 (8%), respectively; and 27 patients (51%) had diffuse-type histology. A total of 29 patients (56%) had ascites. Prior nivolumab therapy was administered to 49 patients (92%). The response rate and disease control rate (DCR) were 2% and 35%, respectively. The median progression-free survival was 2.4 months, and OS was 5.8 months. Patients with ascites exhibited significantly shorter OS (8.6 vs 4.7 months, P = .0291) than those without ascites, and DCR (54% vs 18%, P = .0055) was significantly worse in patients with ascites. There was no significant difference in the frequency of adverse events of grade 3 or higher between patients with and without ascites. Conclusion: In a real-world setting, FTD/TPI has similar effectiveness as late-line chemotherapy for patients with AGC, including those who previously had received nivolumab.